A proposed simulation optimization model framework for emergency department problems in public hospital - Ibrahim, Ireen Munira; Liong, Choong-Yeun; Abu Bakar, Sakhinah; Ahmad, Norazura; Najmuddin, Ahmad Farid (2015)
The Emergency Department (ED) is a very complex system with limited resources to support increase in demand.ED services are considered as good quality if they can meet the patient’s expectation.Long waiting times and length of stay is always the main problem faced by the management.The management of ED should give greater emphasis on their capacity of resources in order to increase the quality of services, which conforms to patient satisfaction.This paper is a review of work in progress of a study being conducted in a government hospital in Selangor, Malaysia.This paper proposed a simulation optimization model framework which is used to study ED operations and problems as well as to find an optimal solution to the problems. The integration of simulation and optimization is hoped can assist management in decision making process regarding their resource capacity planning in order to improve current and future ED operations.